Pendidikan Holistik: Pendekatan Pembelajaran Untuk Membentuk Peserta Didik Yang Berkarakter - Juhra, Al (Indonesian Journal of Teaching and Teacher Education, 2025)
This study aims to analyze the concepts, principles, benefits, and challenges of implementing holistic education as a learning approach to shape students with strong character. Holistic education is considered highly relevant in addressing the challenges of globalization, as it not only emphasizes academic achievement but also fosters emotional, social, physical, and spiritual development. The research employed a literature review method by examining various studies and practices of holistic education, including nature-based schools, the Montessori method, and project-based learning. The findings indicate that holistic education can cultivate balanced, creative, and adaptive learners equipped with essential life skills such as empathy, collaboration, and environmental awareness. Nevertheless, several challenges remain, including limited teacher training, unequal access to educational infrastructure in remote areas, and parental mindsets that prioritize academic rankings over character building. To overcome these issues, proposed solutions include teacher training in holistic pedagogy, collaboration with NGOs in school development, and parental awareness programs highlighting the importance of academic and non-academic balance. With strong commitment from government, schools, and communities, holistic education can serve as a transformative strategy to prepare competent and character-driven future generations.